Comparison of the Effectiveness of Platelet-Rich Plasma, Corticosteroid, and Physical Therapy in Subacromial Impingement Syndrome - Tuğçe PASİN,; Safinaz ATAOĞLU,; Özge PASİN,; Handan ANKARALI, (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate and compare the efficacy of platelet-rich plasma (PRP) injection, corticosteroid injection, and physical therapy in addition to exercise treatment on pain, shoulder functions, and quality of life in patients with subacromial impingement syndrome (SAIS). Patients and methods: Ninety patients (37 males, 53 females; mean age 48.99 years; range, 33 to 60 years) who were diagnosed as Stage 2 SAIS were included in the study. Patients were randomized into three groups. PRP injection was administered into the subacromial space of the affected shoulder in group 1, corticosteroid injection was administered in the subacromial joint space in group 2, and 10 sessions of physical therapy were given in group 3 five times weekly including transcutaneous electrical nerve stimulation, ultrasound, and hot packs. Moreover, an exercise program was administered in all groups. Visual Analog Scale (VAS) was used to determine the resting and moving shoulder pain; while the Shoulder Disability Questionnaire, Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire, and the University of California, Los Angeles Shoulder Rating Scale (UCLA SRS) were used to evaluate the functionality of patients. Quality of life was analyzed using a generic Short Form 36 (SF-36). Results: All scores improved in all three groups compared with the period before treatment. Comparison of the groups showed higher scores in group 1 compared to groups 2 and 3 at week eight on QuickDASH, UCLA SRS, VAS at rest and during activity, and SF-36 pain subgroup scores. Conclusion: All three treatment modalities were effective in the treatment of SAIS. However, we suggest that the inexpensive and noninvasive methods of physical therapy and exercise should be the first preferred treatment in SAIS owing to causing no adverse events.